Brief Behavioral Intervention to Improve Adolescent Sexual Health: A Feasibility Study in the Emergency Department. Issue 1 (January 2016) - Miller, Melissa K.; Champassak, Sofie; Goggin, Kathy; Kelly, Patricia; Dowd, M. Denise; Mollen, Cynthia J.; Humiston, Sharon G.; Linebarger, Jennifer; Apodaca, Timothy
Abstract : Objective: Although emergency department (ED) visits offer an opportunity to deliver brief behavioral interventions to improve health, provision of ED-based interventions targeting adolescent sexual health is uncommon. The objectives for this study were to evaluate the feasibility and preliminary effects of a novel sexual health service intervention for adolescents. Methods: In this cross-sectional feasibility study, sexually active patients aged 14 to 19 years presenting to a Midwestern pediatric ED were recruited to receive an intervention to improve sexual health. The intervention, based on motivational interviewing (MI), included agenda setting, exploration of behaviors, a decisional balance exercise, tailored feedback, and provision of personalized health services (including condoms, prescription for emergency contraception, urine testing for Chlamydia trachomatis and Neisseria gonorrheae, and referral to the hospital-affiliated adolescent clinic). Data were collected before and after intervention administration and at a 3-month follow-up telephone interview. Surveys assessed sexual risk behaviors, satisfaction with the intervention, health care use, and demographics. Feasibility criteria were (1) subject-rated interventionist fidelity to MI principles (Likert scale 1 [strongly agree] to 4 [strongly disagree]), (2) subject satisfaction (Likert scale 1 [not at all] to 5 [very]), and (3) session duration (minutes, recorded by the interventionist). A secondary outcome was the proportion of subjects who completed at least 1 health service. Services provided at the adolescent clinic were determined by an electronic medical record review. Comparisons of responses between sex subgroups were analyzed using Χ 2 test. Results: From August to November 2012, 69 adolescents were approached, 66 (96%) completed the screening survey, and 24 (37%) reported previous sexual activity. Of those, 20 (83%) agreed to participate. The mean (SD) age was 16.2 (1.4) years; 60% were female. Most (78%) reported that the interventionist maintained high fidelity to MI principles and most (80%) were very satisfied with the intervention. Mean (SD) intervention length was 15.7 (2.2) minutes. Most subjects (65%) accepted 1 or more health services, including 42% who completed clinic follow-up. In the ED or the referral clinic, the following services were provided to the subjects: condoms (n = 11), emergency contraception prescription (n = 5), C. trachomatis / N. gonorrheae testing (n = 4), hormonal birth control provision (n = 2), and human immunodeficiency virus testing (n = 3). Fifteen subjects (75%) were reached for the 3-month follow-up, and condom use was maintained by 67% of those reporting sexual activity. Conclusions: This study demonstrated the feasibility and potential utility of an MI-based service navigation intervention to connect youth with point-of-care services as well as resources for ongoing sexual health needs.